Protective effect of Naoxintong against cerebral ischemia reperfusion injury in mice. (22nd April 2016) - Xue, Jing; Zhang, Xiangjian; Zhang, Cong; Kang, Ning; Liu, Xiaoxia; Yu, Jingying; Zhang, Nan; Wang, Hong; Zhang, Lan; Chen, Rong; Cui, Lili; Wang, Lina; et al.
Abstract: Ethnopharmacological relevance: Naoxintong (NXT), a renowned traditional Chinese medicine in China, has been used for the treatment of acute and chronic cardio-cerebrovascular diseases in clinic for more than 20 years. Aim of the study: To evaluate the potential neuroprotective effect of NXT against ischemia reperfusion (I/R) injury in mice and investigate the underlying mechanisms. Materials and methods: Focal cerebral I/R injury in adult male CD-1 mice was induced by transient middle cerebral artery occlusion (tMCAO) for 1 h followed by reperfusion for 23 h. Mice were randomly divided into five groups: Sham group; tMCAO group; Vehicle group; NXT-treated groups at doses of 0.36 g/kg and 0.54 g/kg. The effects of NXT on murine neurological function were estimated by neurological defect scores, infarct volume and brain water content at 24 h after tMCAO. Immunohistochemistry and Western blot were used to detect the expression of LOX-1, pERK1/2 and NF-κB at 24 h after tMCAO. qRT-PCR was used to detect the expression of LOX-1 and NF-κB at 24 h after tMCAO. Results: Compared with Vehicle group, 0.54 g/kg group of NXT significantly ameliorated neurological outcome, infarction volume and brain water content, decreased the expression of LOX-1, pERK1/2 and NF-κB ( P <0.05). Conclusion: NXT protected the mice brain against I/R injury, and this protection maybe associated with the down-regulation of LOX-1, pERK1/2 and NF-κB expression. Graphical abstract: